Nanostructural crystallization of cast iron - E. I. Marukovich; V. Yu. Stetsenko; A. V. Stetsenko (Литьë и металлургия)
Crystallization of cast iron has been shown to be a nanostructured process. Austenitic-graphite eutectic is formed from iron and graphite nanocrystals, free iron and graphite atoms. Austenitic-cementite eutectic is formed from iron and graphite nanocrystals, free graphite atoms and iron-carbon complexes. Primary austenite microcrystals are formed from iron nanocrystals, graphite and iron-carbon complexes.